The Influence of Corporate Governance on Companies Profitability with Capital Structure as Intervening - Auwal Salisu; Nindi Riyana Saputri (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
The study's goal is to examine if the structure, process, or principle has a role in corporate governance in terms of increasing profitability. This research use quantitative methodologies in conjunction with descriptive data analysis. Non-random sampling was used to determine the research sample. The study included a total population of 469 firms, with 18 organizations being sampled each year in line with the study. Secondary data on ROA, corporate capital structure, board size, board independence, and audit committee, as well as company financial reports (annual reports) in the form of audit repute and ownership concentration, was accessible through Bloomberg. The first equation is the relationship between capital structure and company profitability, and it is concluded that there is no relationship between board size and ownership concentration on the capital structure of the company, but an independent board, audit committee, and reputation audit show the opposite results. The second equation investigates the relationship between corporate governance and capital structure and profitability, concluding that there is a link between board independence, audit reputation, ownership concentration, and capital structure and company profitability, but no link between board size and audit committee. According to the results of the mediation test (using the Sobel test), the capital structure acts as an intermediary variable between board independence and audit committee on profitability, but it has no influence on board size, audit committee, or ownership concentration on profitability.